2020
DOI: 10.2174/1570159x18666200729093724
|View full text |Cite
|
Sign up to set email alerts
|

The Links between Cardiovascular Diseases and Alzheimer's Disease

Abstract: : The root cause of non-inherited Alzheimer’s disease (AD) remains unknown despite hundreds of research studies performed to attempt to solve this problem. Since proper prophylaxis remains the best strategy, many scientists have studied risk factors that may affect AD development. There is robust evidence supporting the hypothesis that cardiovascular diseases (CVD) may contribute to AD progression; the diseases often coexist. Therefore, a lack of well-defined diagnostic criteria makes studying the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 214 publications
(263 reference statements)
2
21
1
Order By: Relevance
“…Increasing age is a major risk factor for Alzheimer’s disease (AD) and the most common form of dementia [ 178 ]. Aging is known to be associated with increasing incidence of hypertension and type 2 diabetes mellitus that are believed to enhance the risk of Alzheimer’s disease [ 179 , 180 , 181 ]. In view of the close association between insulin resistance and decreased cerebral glucose metabolism with Alzheimer’s disease, it has been argued that Alzheimer’s could be considered as a type 3 diabetes mellitus [ 182 ].…”
Section: Alzheimer’s Disease and Balsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing age is a major risk factor for Alzheimer’s disease (AD) and the most common form of dementia [ 178 ]. Aging is known to be associated with increasing incidence of hypertension and type 2 diabetes mellitus that are believed to enhance the risk of Alzheimer’s disease [ 179 , 180 , 181 ]. In view of the close association between insulin resistance and decreased cerebral glucose metabolism with Alzheimer’s disease, it has been argued that Alzheimer’s could be considered as a type 3 diabetes mellitus [ 182 ].…”
Section: Alzheimer’s Disease and Balsmentioning
confidence: 99%
“…Such a purported relationship between T2DM and AD led to the use of intranasal insulin in its (AD) treatment resulted in controversial results [ 183 ]. Furthermore, changes in lipid metabolism in brain regions that play a significant role in cognitive function [ 184 , 185 ] which is reflected in the periphery [ 181 ] and with age have been described [ 186 ]. In a recent study that was coined to evaluate age-related changes in the lipidome of the rat amygdala obtained from young (3 months) and old (20 months) males of the Sprague-Dawley rats, significant changes in the levels of four main lipid classes: glycerolipids, glycerophospholipids, sphingolipids and sterol lipids was described [ 184 ].…”
Section: Alzheimer’s Disease and Balsmentioning
confidence: 99%
“…Professor Aliev possessed an encyclopedic knowledge in a wide range of scientific fields; however, his main research focus was linked to the development of unique technologies and treatment protocols for age-associated diseases. He was recognized internationally for his work in the fields of gerontology [ 1 , 2 , 3 , 4 , 5 ], oncology [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], cardiovascular diseases [ 16 , 17 , 18 , 19 ], endocrinology [ 2 , 20 , 21 ], and neurodegenerative diseases [ 15 , 20 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. His research publications on the role of vascular and mitochondrial factors in the pathogenesis of aging [ 2 , 3 , 5 ], atherosclerosis [ 33 , 34 ], ischemia-reperfusion [ 18 , 35 , 36 , 37 ], stroke [ 4 , 18 , 35 , 38 ], and Alzheimer’s disease (AD) [ 23 , 24 , 33 ,…”
mentioning
confidence: 99%
“…For instance, his in vitro cancer cell model for the peptide based new drug development study showed promising results regarding the specific delivery of drugs to tumor tissues [63,65]. Another of his in vivo studies found that nanoparticles are able to cross the blood-brain barrier, which has been the biggest impediment in delivering drugs to patients with Alzheimer's disease [16,18,64].…”
mentioning
confidence: 99%
See 1 more Smart Citation